Menulusuri Aspek Maritim Sungai Musi Untuk Pembelajaran Sejarah Lokal - Aulia Novemy Dhita; Muhammad Reza Pahlevi (CHRONOLOGIA, 2023)
The Musi River has an important role in historical periodization in Palembang, especially during the Srivijaya period. However, the role of the Musi river has not been conveyed so often in the concept of learning local history and its relation to maritime affairs. Based on these conditions, this study aims to examine the maritime aspects of the Musi River as a means of learning local history. The method used is a qualitative method using a historical approach. The role of the Musi river in Indonesian maritime needs to be developed for learning local history. This is very important because Sriwijaya's maritime glory was also influenced by the Musi river. This role can be explained through maritime aspects, namely trade, shipping, shipping, maritime traditions, sea mythology, piracy, fisheries, law of the sea. Based on exploring these maritime aspects, the material on the Musi river becomes broader and contextual to be applied in learning local history based on the basic competencies of the curriculum.